Chicken-Derived Pattern Recognition Receptor chLGP2 Inhibits the Replication and Proliferation of Infectious Bronchitis Virus - Wang, Kailu; Cui, Pengfei; Ni, Ruiqi; Gong, Huiling; Li, Hao; Yan, Wenjun; Fu, Xue; Chen, Liang; Lei, Changwei; Wang, Hongning; Yang, Xin (Frontiers in Microbiology, 2022)
The widespread nature and economic importance of IBV and interactions between IBV and the host immune response remain poorly understood. Understanding the mechanism of virus recognition via innate immunity can help resist IBV invasion. RLRs recognize virus RNA in virus infection, and LGP2 is a member of RLRs. According to the current studies, LGP2 exhibited certain inhibition in the virus, and there is a lack of investigation for chicken's LGP2. It is important to figure out the role of chLGP2 in host immune recognition of IBV. Our results showed that chLGP2 inhibited the proliferation of IBV Beaudette in cells. Also, chLGP2 can identify and combine with IBV RNA. The domains of chLGP2 were separately expressed and inspired by related literature, and the chLGP2 K30A mutant was constructed. Our results suggested its structural integrity and the ATPase activity are critical for IBV inhibiting activity. chTRBP was selected after CO-IP and Mass spectrometry test. We found chTRBP and chLGP2 are the interacting partners and promote mutual expression. Our study showed that chTRBP could also suppress IBV infections via chLGP2, which provided a basis for future innate immunity research for IBV.